2019
DOI: 10.13005/bpj/1786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective effect of hydroalcoholic extract of Momordica Charantia leaves in carbon tetrachloride induced liver toxicity in Wistar rats

Abstract: Liver carries out a variety of physiological functions and protects against damaging drugs and chemicals. Herbs have been shown to play a major role in the management of various liver disorders. Due to the lack of effective liver protective medication in modern medicine, several herbal options for the treatment of liver diseases in Ayurveda are suggested. In this current study, we evaluated the hepatoprotective action of Momordica charantia leaf extract in comparison to Liv-52, a standard hepatoprotective drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“… [ 157 ] Momordica charantia Linn. (Cucurbitac-eae) Hydro-alcoholic extract of Leaves Rats Carbon tetrachloride 100 & 200 mg/kg Total bilirubin↓, ALP↓, SGPT↓, SGOT↓ Antimicrobial [ 158 ] Momordica dioica (Cucurbita-ceae) Ethanolic and aqueous extract of Leaves Rats Carbon tetrachloride 200 mg/kg AST↓, ALT↓, ALP↓, total bilirubin (TB)↓ Used in head trouble, urinary calculi, tridosha, fever, asthma, bronchitis, high cough and piles. Aphrodisiac and anthelmintic.…”
Section: Hepatoprotective Potentials Of Medicinal Plants and Their Bi...mentioning
confidence: 99%
“… [ 157 ] Momordica charantia Linn. (Cucurbitac-eae) Hydro-alcoholic extract of Leaves Rats Carbon tetrachloride 100 & 200 mg/kg Total bilirubin↓, ALP↓, SGPT↓, SGOT↓ Antimicrobial [ 158 ] Momordica dioica (Cucurbita-ceae) Ethanolic and aqueous extract of Leaves Rats Carbon tetrachloride 200 mg/kg AST↓, ALT↓, ALP↓, total bilirubin (TB)↓ Used in head trouble, urinary calculi, tridosha, fever, asthma, bronchitis, high cough and piles. Aphrodisiac and anthelmintic.…”
Section: Hepatoprotective Potentials Of Medicinal Plants and Their Bi...mentioning
confidence: 99%
“…The leaf decoction is used to treat diabetes and malaria in Nigeria (Ediriweera et al, 2017) Pulp extract combined with lupeol Induced hepatoprotective effect against 7, 12dimethylbenzanthracene induced liver alteration in Swiss albino mice (Shah et al, 2010) Studies have reported the lack of toxic effect although minimal toxic effect on seed kernel has been reported (Derese et al, 2017) Momordica charantia L It is used to treat jaundice in India. It is also used to treat hepatitis (Grover and Yadav, 2004) Hydroalcoholic leaf extract induced hepatoprotective effect against CCl4 induced hepatotoxicity in rats (Moharir et al, 2019) The plant is relatively safe as no toxicity is reported in experimental animals when administered at low dose for up to 2 months (Grover and Yadav, 2004) Moringa oleifera Lam.…”
Section: Ph Ravenmentioning
confidence: 99%
“…Mặc dù y học hiện đại đã đạt được những bước tiến lớn, song phương pháp điều trị cũng như lựa chọn thuốc điều trị các bệnh về gan hiện vẫn còn nhiều hạn chế. Bên cạnh đó, một số thuốc có nguồn gốc hóa dược dùng trong điều trị bệnh gan cũng có khả năng gây tổn thương gan [1], [2]. Vì vậy, các nghiên cứu về dược liệu có tác dụng dự phòng và điều trị bệnh gan là vấn đề quan trọng và cần thiết.…”
Section: đặT Vấn đềunclassified